Thermal Performance Enhancement of Phase Change Materials (PCMs) by Using Metal Foams - Hussain, Ihsan Y.; Jasim, Marwah Abdulkareem (Al-Nahrain Journal for Engineering Sciences, 2017)
An investigation of thermal conductivity enhancement, melting and solidification processes of Phase Change Materials (PCMs) by using metal foams has been carried out. Two models have been used in the experiments, model I for measuring the effective thermal conductivity of metal foam embedded in paraffin wax, and model II used as a small scale thermal energy storage device with and without metal foam for investigating melting and solidification processes of the PCM under different cooling conditions (natural and forced convection). The theoretical investigation involves analytical solution of two models, the semi-infinite medium for calculating the thermal conductivity, and the thermal energy storage system TESS has been analyzed including several assumptions for determining the convective heat transfer coefficient and the factors that controlling forced convection and solidification of the PCM. The experimental results show that the thermal conductivity of wax with 10 PPI metal foam increased by (37-39) times that of pure wax. Effects of pore density (10 and 40 PPI), metal foam, and mass flow rate on solidification process have been studied and the effects of pore density and metal foam on the melting process have also been investigated. The present experimental results have been compared with the available previous studies and gave a good agreement.